Assessment of radioactivity contents in bedrock groundwater samples from the northern region of Saudi Arabia - Almasoud, F. I.; Ababneh, Z. Q.; Alanazi, Y. J.; Khandaker, Mayeen Uddin *; Sayyed, M. I. (Elsevier, 2020)
Recognizing the vast uses of water in human life, the presence of α and β particles emitting radionuclides in groundwater of northern Saudi Arabia has been evaluated as a means of water quality assessment of the region. A liquid scintillation counting technique was used to determine the gross α/β, and 228Ra radioactivities in water samples, while the radioactivity concentrations of 234,238U and 226Ra were determined using alpha spectrometry after the separation process. Present results show that all water samples contain a higher level of gross α and β radioactivity than the WHO recommended limits; the average gross α activity is about 7 times greater than the limit value of 0.5 Bq L−1, while the average gross β activity value is about 3.5 times greater than the limit value of 1 Bq L−1. Correlations of TDS and pH with gross α and β radioactivity in the studied samples were investigated. The activity ratio of the measured U and Ra alpha emitters to the gross α radioactivity and the ratio of the measured β emitters to gross β radioactivity were also discussed. Furthermore, interesting information on thorium abundance and radioactive disequilibrium in U series were observed by studying the activity ratio of 228Ra/226Ra, 226Ra/238U, and 234U/238U. Although these samples are not directly used for human being drinking, and mainly used in irrigation, the higher gross α/β radioactivity may cause health risks to humans, since these radionuclides may enter the food chain through irrigation water. Thus, further radioactive risk assessment is highly recommended.